The Role of International Humanitarian Law in the Conflict with the West Papua Liberation Army - Sudirman, Muhammad Uchida (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2025)
This research examines the application of International Humanitarian Law (IHL) in the conflict between the Indonesian National Armed Forces (Tentara Nasional Indonesia, or “TNI”) and the West Papua National Liberation Army (TPNPB). The main focus is to assess the legal status of TPNPB as a non-state armed actor and examine the extent to which the TNI's authority in military operations has been in accordance with the principles of proportionality, distinction, and precaution. Using qualitative legal research and conceptual, statutory, and historical approaches, the findings indicate that the conflict in Papua has fulfilled the elements of a non-international armed conflict (NIAC), although it has not been officially recognized by the Indonesian government. In addition, the implementation of TNI's authority in Military Operations Other Than War (OMSP) is considered to have the potential to violate IHL principles because of its impact on civilians. This research recommends a more consistent application of IHL to ensure the effective protection of civilians in domestic conflicts.